Infectious disease physician characteristics and prescription of meropenem in the hospital - Douglas Challener; John O'Horo; Aaron J. Tande (Cambridge University Press, 2023)
Abstract Objective: Physician characteristics may be correlated with medical treatment decisions and patient outcomes. This study examined the correlations between characteristics of infectious disease (ID) physicians and the use of the restricted antimicrobial meropenem. Design: This was a retrospective cohort study following 27 attending ID physicians for 5 years at a large academic medical center. Methods: All inpatient ID clinical encounters between 2013 and 2018 were assessed for physician and patient characteristics, including patient Charlson Comorbidity Index, patient sex, ID service seeing the patient, physician career stage, physician training location, and physician sex. Adjusted and unadjusted odds ratios were calculated for the receipt of meropenem on the same day as an ID clinical note. Results: Between 2013 and 2018, meropenem was administered on the same day as 9046 (11.1%) of 81,787 inpatient ID encounters. After adjustment for patient and practice-specific factors, physician career stage was associated with administration of meropenem. Patients seen by mid-career and late-career ID physicians were more likely to receive meropenem than those seen by early-career physicians (aOR 1.22 95% confidence interval [CI 1.13-1.31 and aOR 1.17 95% CI 1.10-1.25, respectively). Conclusions: ID provider characteristics may help target future antimicrobial stewardship program interventions.